LANGUAGE AND STYLE OF JAMES JOYCE (American Journal of Research in Humanities and Social Sciences, 2023)
This article includes information on literary language and writing style of James Joyce with precise facts. Major works of James Joyce such as Dubliners and Ulysses are analyzed. His distinctive use of the language and contribution to the Modernism will be explained.